Peningkatan Meaning Life Bagi Wanita Terlambat Menikah Melalui Konseling Realita - Azmatul Khairiah Sari; Triave Nuzila Zahri; Al Ikhlas (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2023)
Life is something that every individual should be grateful for. In life we will face various problems and problems. With problems and problems in the end will make us understand the Meaning Of Life. One of the problems faced for individuals is late marriage. The existence of negative assumptions in women who are late in marriage is something that is feared by these women. This fear ultimately has an effect on the formation of Meaning of Life in the woman. Not a few women who are late in marriage form a low and negative Meaning of Life in themselves. The importance of a positive and good Meaning of Life in oneself will certainly make oneself more productive and enthusiastic in one's daily life. Counseling is one solution in the formation of a good and positive Meaning of Life in women who are late in marriage. The approach that can be used by counselors is with a reality counseling approach. In the reality counseling approach, invite clients to be able to accept positively and responsibly the life they live. Counseling is one solution in the formation of a good and positive Meaning of Life in women who are late in marriage. The approach that can be used by counselors is with a reality counseling approach. In the reality counseling approach, invite clients to be able to accept positively and responsibly the life they live. This study uses case studies to illustrate how the Meaning of Life faced by the client and how reality counseling can direct the Meaning of Life of the client to be more positive than before. And it can be concluded that reality counseling can change the Meaning of Life of a woman who is late to marry to be more positive and she respects herself more.